Increasing Organizational Citizenship Behavior Through Strengthening Transformational Leadership in High School Teachers - Rohimah; Bibin Rubini; Widodo Sunaryo (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2022)
Building human resources is a major responsibility of a country and it is a process that must be carried out sustainably, starting from the preschool, primary, secondary, and tertiary levels. The level of learning cannot guarantee the competitive advantage of human resources in Indonesia to compete against other countries in this era of global competition. One of the government's ways to balance the competition is to create a nine-year compulsory education program while improving systems, facilities, and infrastructure in educational institutions. Human resources or foreign terms are often referred to as "Human Resources" and are one of the main elements of a system that exists within a company or organization. In achieving organizational success, it does not only require qualified and competitive people but also requires resources that have a behavior that is then referred to as Organizational Citizenship Behavior (OCB). OCB itself can improve job performance because this behavior is the lubricant of the social engine in the organization. The reality in the field is that someone who is a teacher does not yet understand and have Organizational Citizenship Behavior (OCB) in school organization. This research is expected to find the efforts that are practiced to improve the Organizational Citizenship Behavior of teachers by identifying and developing the variables that affect the Organizational Citizenship Behavior of teachers, especially the transformational leadership variable.